O ensino de Biologia no Cursinho Popular de Altamira - PEREIRA, Thaís Nascimento (2022)
This text aims to present an analysis of the methodology used in teaching Biology at your local community college Popular of Altamira by means of Popular Education. The main hypothesis is that the method freirean allied to the teaching of Biology helps in the formation of social subjects more engaged in issues relevant to society. This method consists in the work of encoding and decoding of a particular content, covering its social problems. This study showed the importance of a differentiated teaching Biology,that load in addition to preparing the formal labour market, preparation for life. Through research, it was possible to realize that the application of the method of Popular Education in the classroom provided an elevation in the level of consciousness of learners, that during the study, showed interest in participating in social, environmental and educational.